2017
DOI: 10.1016/j.ijbiomac.2017.03.087
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the link between antimicrobial properties of dietary olive phenolics and bacterial ATP synthase

Abstract: The naturally occurring olive phenolics tyrosol, hydroxytyrosol, dihydroxyphenylglycol (DHPG), and oleuropein are known to have antioxidant, antitumor, and antibacterial properties. In the current study, we examined whether the antimicrobial properties of tyrosol, hydroxytyrosol, DHPG, and oleuropein were linked to the inhibition of bacterial ATP synthase. Tyrosol, hydroxytyrosol, DHPG, and oleuropein inhibited Escherichia coli wild-type and mutant membrane-bound F1Fo ATP synthase to variable degrees. The grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 74 publications
(103 reference statements)
1
22
0
Order By: Relevance
“…From the microbiological perspective, the antimicrobial substances contained in acid whey and lemon juice, such as organic acids, whey protein, bacteriocins and polyphenols, were responsible for the inhibition of microbial growth. The pH reduction caused by organic acids (citric, lactic) was the primary factor that affected the reduction of microorganisms (Ahmad et al, 2017;Alvadaro and Mc Kee 2007;Amini et al, 2017). In the present study it was shown that after thermal treatment no aerobic bacteria were found in both the control group and in WM and LJM.…”
Section: Resultssupporting
confidence: 46%
“…From the microbiological perspective, the antimicrobial substances contained in acid whey and lemon juice, such as organic acids, whey protein, bacteriocins and polyphenols, were responsible for the inhibition of microbial growth. The pH reduction caused by organic acids (citric, lactic) was the primary factor that affected the reduction of microorganisms (Ahmad et al, 2017;Alvadaro and Mc Kee 2007;Amini et al, 2017). In the present study it was shown that after thermal treatment no aerobic bacteria were found in both the control group and in WM and LJM.…”
Section: Resultssupporting
confidence: 46%
“…The extent of inhibition is directly proportional to the molecular level interactions which depend on the interaction between functional groups of inhibitors and binding site amino acids of ATP synthase. The molecular-level interactions between inhibitors and binding-site residues have been resolved for some and are under investigation for many [ 10 - 12 , 20 - 25 ].…”
Section: Atp Synthasementioning
confidence: 99%
“…The apoptotic mechanism of action of apoptolidin is through selective inhibition of F 1 F o ATP synthase [ 66 , 67 ]. Selective ATP synthase inhibition has been attributed to the type and position of amino acids in and around the inhibitor binding sites [ 22 , 25 ]. Slight variation in amino acids was shown to cause selective and specific inhibition of ATP synthase from a variety of food sources.…”
Section: Atp Synthase As a Molecular Drug Targetmentioning
confidence: 99%
“…Additionally, numerous biologic activities have been ascribed to HT, although in some cases its mechanism of action has not been clarified. Of particular interest are the anti-inflammatory and antimicrobial properties of HT, which have been described in many diseases [ 28 , 31 , 32 , 33 , 34 , 35 , 36 ]. In particular, it has been reported that HT was able to inactivate the staphylococcal enterotoxin A, a key factor in the patho-physiology of animal mastitis [ 37 ].…”
Section: Introductionmentioning
confidence: 99%